TOKOH DAN PENOKOHAN DALAM TEKS CERITA FANTASI KARYA SISWA KELAS VII SMP NEGERI 21 PADANG DAN IMPLIKASINYA TERHADAP PEMBELAJARAN TEKS CERITA FANTASI DI SMP - Ningsih, Cahyu; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTÂ This article reveals the types of characters and characterizations in the text of fantasy stories for Grade VII students of SMP Negeri 21 Padang. There are two objectives of this research. First, describe the types of characters that the seventh grade students of SMP Negeri 21 Padang appear in in the text of the fantasy stories they write. Second, to describe the character presence techniques used by SMP Negeri 21 Padang students to bring out the character of the characters in the fantasy stories they write. This type of research is qualitative research with descriptive methods. The main instrument of this research is the researcher himself. Data were collected using documentation techniques, which are still archived by Indonesian language subject teachers. There are two findings in this study, namely (1) the types of figures that students tend to appear in the text of the fantasy stories they write are fictional characters, additional characters, protagonists, white characters, flat characters, and static characters, but other types of characters. students still use them in the text of their fantasy stories, and (2) the techniques for the presence of figures that are often used by students are analytical techniques, action techniques, and word techniques. However, the students still use the technique of the presence of other figures.Â Kata kunci : tokoh, penokohan, teks cerita fantasiÂ